Pemberdayaan Ekonomi Perempuan Pedesaan Melalui Hilirisasi Komoditas Cabai: Asesmen Kesiapan Kelompok Wanita Tani dan Perancangan Model Bisnis Berkelanjutan di Dukuh Diran, Kulon Progo - Kurniawan Chandra Wijaya; Ma'un Budiyanto; Stella Maria Lourdes Kusumawardhani (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
Chili downstreaming into packaged chili paste is proposed as a strategy to mitigate price volatility that undermines farmers’ income stability in Kulon Progo. This mixed-method study evaluates the readiness of the Women Farmers Group (KWT) in Dukuh Diran using a validated survey instrument (α = 0.906) alongside the design of a digital-based business model. The findings reveal that the community possesses strong social capital, reflected in high levels of social support (x ̄ = 3.77) and entrepreneurial attitude (x̄ = 3.50), although market access (x̄ = 3.30) remains a key constraint. Statistical analysis confirms that entrepreneurial attitude (rₛ = 0.876) and social support (rₛ = 0.836) are the strongest predictors of business commitment among KWT members. Financially, the proposed “Sambal Miss Ti” business model is highly feasible, with an R/C ratio of 1.47 and a low Break-Even Point (BEP) of only 1.05 units. Furthermore, the implementation of a web-based business calculator proved effective in preventing pricing errors caused by volatile raw material costs. It is concluded that the success of chili downstreaming depends on the integration of strong community support and the utilization of digital decision-support tools.